(untitled) (Mustansiria Dental Journal, 2024)
This study was designed to determine the type and prevalence of trumatic dental injuries, aenterio—posterior molar relation among (519) deaf persons and (532) school students at 5-16 years of age in the middle region of Iraq. The study showed that the prevalence of traumatic dental injuries were 6.94% for deaf persons and 5.83% for schools students. Males showed a higher percentage of traumatized teeth than females in institutions and school students. Enamel dentine fracture without pulp exposure was the most predominant type among deaf persons while simple enamel fracture was the most predominant among schools students. The majority of deaf persons and schools students demonstrated normal type of occlusion 57.42%, 55.64% respectively. Deaf person showed significantly with percentage of 4.62% mesial full cusp deviation from normal .antero·postrior molar relation compared to school students 2.07%